2010
DOI: 10.2133/dmpk.dmpk-10-rg-044
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Diosmetin and Hesperetin are Potent Inhibitors of Cytochrome P450 2C9-mediated Drug Metabolism in vitro

Abstract: The aim of this study was to examine in vitro, by means of kinetic analysis and molecular docking simulations, the effects of the flavone diosmetin and its flavanone analog hesperetin on CYP (cytochrome P450) 2C9-mediated drug metabolism. To this purpose, the conversion of diclofenac to 4'-hydroxydiclofenac by human liver microsomes was used as a model assay for assessing the CYP2C9 inhibitory activity of these two flavonoids. Kinetic analyses showed that diosmetin and hesperetin were reversible, dead-end inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 45 publications
0
17
0
3
Order By: Relevance
“…A number of clinical trials have been conducted using large doses of flavonoids for disease prevention, and there were no serious side effects observed in these studies (19). However, it has been confirmed that several flavonoids are potent inhibitors of CYP2C-mediated drug metabolism (20,21) and thus possess the potential to alter the efficacy of some prescribed drugs (22). Although concomitant administration of high flavonoid-containing substances with therapeutic agents carries the risks of unwanted interactions, these plant-derived compounds may also markedly improve the bioavailability of some orally administered drugs.…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical trials have been conducted using large doses of flavonoids for disease prevention, and there were no serious side effects observed in these studies (19). However, it has been confirmed that several flavonoids are potent inhibitors of CYP2C-mediated drug metabolism (20,21) and thus possess the potential to alter the efficacy of some prescribed drugs (22). Although concomitant administration of high flavonoid-containing substances with therapeutic agents carries the risks of unwanted interactions, these plant-derived compounds may also markedly improve the bioavailability of some orally administered drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Some research has demonstrated the ability of hesperidin or its metabolites to inhibit some hepatic isoenzymes of the cytochrome P-450 [42,43]. Such as cisplatin is a drug which has no known interactions with cytochrome P450 enzymes [44][45][46], it is supposed that hesperidin does not act at the hepatic level, under these experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] However, the effects of HET and NGR on UGT activity have not been fully characterized. Understanding the effects of HET and NGR on UGT activities is important to ensure their safe administration and development new co-administration therapies with both drugs.…”
Section: )mentioning
confidence: 99%